Plate fixation of midshaft clavicle fractures for delayed union and non-union is a cost-effective intervention but functional deficits persist at long-term follow-up. (August 2022) - Fox, Ben; Clement, Nicholas David; MacDonald, Deborah J; Robinson, Michael; Nicholson, Jamie A
Background: The primary aim of this study was to compare the long-term functional outcome of midshaft clavicle fracture fixation for delayed (≥3 month) and non-union (≥6 month) compared to a matched cohort of patients that achieved union with non-operative management. The secondary aim was to assess cost-effectiveness of fixation. Methods: A consecutive series of patients over 10-years were retrospectively reviewed using the QuickDASH, Oxford Shoulder Score and EuroQol five-dimension summary index (EQ-5D). These patients were compared to a matched cohort that achieved union after non-operative management using propensity score matching. Results: Sixty patients (follow-up 79%, n = 60/76) at 4.1 years post-operative (1.1–10.0 years) had a QuickDASH of 16.5 (95% CI 11.6–21.5), Oxford Shoulder Score 41.5 (39.0–44.1) and EQ-5D 0.7621 (0.6822–0.8421). One in five patients were dissatisfied with their final outcome ( n = 13/60). Functional outcome was inferior following fixation when compared to patients that united with non-operative management (QuickDASH 16.5 vs. 5.5, p < 0.001 and EQ-5D 0.7621 vs. 0.9073, p = 0.001). However, significant improvements were found when compared to pre-operative scores (QuickDASH p < 0.001 and EQ-5D p < 0.001). The cost per QALY for fixation was £5624.62 for the study cohort. Conclusions: Clavicle fixation for delayed and non-union is a cost-effective intervention but outcomes are worse compared to patients that unite with non-operative management.